2018
DOI: 10.1111/bioe.12527
|View full text |Cite
|
Sign up to set email alerts
|

Medical crowdfunding and the virtuous donor

Abstract: Patients and families are increasingly turning to crowdfunding to help them cover the cost of medical care. The ethics of crowdfunding has garnered some attention in the bioethical literature. In this paper I examine an ethical aspect of medical crowdfunding (MCF) that has received limited attention: the role of donors. I defend a virtue ethical approach to analyzing the role of donors in MCF. Vicious donation, where donors do not exercise the relevant virtues, can compound some of the ethical risks associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Liu et al [ 15 ] also revealed that individuals will increase their willingness to donate because of their affective state derived from the concerns of the charitable crowdfunding fundraiser’s situation. Patients can use crowdfunding platforms to connect emotionally with potential donors to raise funds for health care [ 39 ]. Thus, we propose the following hypothesis:…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [ 15 ] also revealed that individuals will increase their willingness to donate because of their affective state derived from the concerns of the charitable crowdfunding fundraiser’s situation. Patients can use crowdfunding platforms to connect emotionally with potential donors to raise funds for health care [ 39 ]. Thus, we propose the following hypothesis:…”
Section: Introductionmentioning
confidence: 99%
“…The health conditions people seek to treat via the funds raised by these campaigns are similarly diverse, crossing the spectrum of chronic and acute conditions as well as medical emergencies (Snyder et al, 2017a(Snyder et al, , 2017b. While medical crowdfunding may have benefits for patients, such as providing financial access to life-saving care, many critics suggest that the considerable turn to crowdfunding for medical needs signals larger systematic and equity concerns (Moore, 2019;Snyder et al, 2017b). One such concern is the growing recognition that certain groups may be less likely to reach their medical fundraising goals than others, including people with limited social networks and those diagnosed with stigmatized illnesses such as lung cancer, mental illness, contested illnesses and HIV/AIDS (Dressler and Kelly, 2018).…”
Section: Health 25(6)mentioning
confidence: 99%
“…One such concern is the growing recognition that certain groups may be less likely to reach their medical fundraising goals than others, including people with limited social networks and those diagnosed with stigmatized illnesses such as lung cancer, mental illness, contested illnesses and HIV/AIDS (Dressler and Kelly, 2018). There are also strong ethical concerns with regard to medical crowdfunding, including that funding platforms actively encourage people to disclose highly personal details of their health status and illness journeys in their narratives that they may not otherwise share with others (Gonzales et al, 2018;Moore, 2019). Scholarly research regarding medical crowdfunding, including explorations of its causes and consequences, is nascent and thus many things remain currently unknown about how and why people opt to participate in this phenomenon as a campaigner or donor.…”
Section: Health 25(6)mentioning
confidence: 99%
“…4 Decision to donate, and hence what to allocate additional funds towards, is not based on priorities, medical conditions or legitimacy of the demands, but on abstract individual preferences that depend on external attributes (for instance, physical appearance, sex, age and race) and the ability to tell a story that appeals to donors' generosity. 6 Medical crowdfunding may further challenge clinicians' authority. This is illustrated by the widely reported case of Charlie Gard, 7 a British child born in 2016 who was diagnosed with a rare genetic disorder at a few months of age.…”
Section: Medical Crowdfunding Raises Equity and Ethical Concernsmentioning
confidence: 99%